¿Black is black? El Caribe y Centroamérica más allá de África y la negritud - Mackenbach, Werner (2016)
In scholarly resarch on the Caribbean it has become a common topic to understand the region in terms of afrodescendencia and négritude (blackness). With that a certain tendency to enclose the so diverse cultural space of the Caribbean and Central America in a new limited and essentialist conception has been taken place, by this prescinding from the multiple and complex processes of transcultural convergency in the course of its history. However, as early as the seventies and eighthies of the XX century have been emerging comprehensive and innovative essays in and from the Caribbean itself that introduce new dimensions in the debates on caribbeaness, antillanité, mestizaje, creoleness, etc. In Caribbean and Central American literatures numerous oeuvres have beenemerging that pick out as a central theme, ironize, and parody the search for an exclusively black identity of the Caribbeans and the efforts to return to “Mother Africa”. This essay presents an analysis of this phenomena in four novels from the francophone and hispanophone Caribbeans: Ti Jean l’horizon (1979) by Simone Schwarz-Bart (Guadaloupe), Calypso (1996) by Tatiana Lobo (CostaRica), Limón Blues (2002) by Anacristina Rossi (Costa Rica) and Black is black (2008) by Raphaël Confiant (Martinique).